PHARMACODYNAMICS OF PROPOFOL INFLUENCE OF GABRE AND ABCB1 GENES - Ivanov, Emilija; Karadjova, Dafina; Sivevski, Atanas; Kokareva, Anita; Pop-Stefanija Corbeva, Vesna; Gjorgjevic, Aleksandra (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
We live in a world where the pharmaceutical industry is experiencing its rise and attention, and every day we face different reactions, different response to different drugs in different people. On the other hand, we are witnessing a wave of encouraging new drugs, especially in the field of oncology, which are based on the concept of individualized therapy. The aim of our study was to investigate the influence of the cytochrome, γ -aminobutyric acid type A (GABAA) receptor γ1 subunit GABRA1 (rs2279020) and ATP-binding cassette sub-family B member 1 ABCB1 (rs1045642) gene polymorphisms on propofol therapeutic outcomes in the patients undergoing abdominal hysterectomy. Ninety patients aged 29-74 years, with different ethnicities were included in this study. The presence of polymorphisms was analyzed using TaqMan SNP genotype analysis on Stratagene MxPro 3005P real-time polymerase chain reaction (qPCR). Our study did not detect a statistically significant influence of the GABRA1 (c.1059+15G>A) and ABCB1 (c.3435T>C) variants on the variability of clinical parameters (doses for induction in anesthesia, additional doses, induction time and wake time after anesthesia and side effects of propofol). The observed trend on the possible influence of the GABRA1 (c.1059+15G>A) and ABCB1 (c.3435T>C) variants warrant an extension of these studies in a larger number of patients.
Keywords: ABCB1 gene; GABRA1 gene; Pharmacogenetic; Propofol